Estratigrafia da memória e do esquecimento: uma análise da coleção afro do Museu Galdino Bicho (IHGSE) - Neco, Douglas Santos (2023)
In the mid-1946s, the Historical and Geographical Institute of Sergipe – IHGSE received a donation of objects of material culture, the result of seizures by the then police chief of the state of Sergipe, objects that came from afro-religious communities in the city of Aracaju/ SE. Soon after receiving them, they were integrated into the collections of the Galdino Bicho Museum, undergoing a process of musealization, these materialities have since then been under the institution's custody. However, even after more than seventy-six years, little is known about these objects. Thus, this dissertation sought through the investigative field to identify, document and highlight this collection by performing a stratigraphy of memories. Taking into account the paths of discursive relations between archeology, heritage and society, it was possible to problematize the uses and management of collections, coming from the archaeological field and/or acquired by other means, being musealized or not in cultural institutions, museums, among others. We base the questions present in this dissertation based on the perspectives that involve the discourse of materialities through the lens of archeology and museology, understanding their interdisciplinarity, highlighting decolonial processes to compose reflections in archeology, and establish processes of social reparation through sensitive goods. In this sense, the decoloniality of thought composes these positions as guides for critical thinking. Within this perspective, it was possible to measure possibilities of resignifications, restitutions that can lead to a process of reparation for historically subaltern Afro-religious communities.